Evaluation of CNN architectures for gait recognition based on optical flow maps - Castro, Francisco M.; Marín-Jiménez, Manuel J.; Guil-Mata, Nicolás; López-Tapia, S.; Pérez de la Blanca, N. (My University, 2017)
This work targets people identification in video based on the way they walk (\ie gait) by using deep learning architectures. We explore the use of convolutional neural networks (CNN) for learning high-level descriptors from low-level motion features (\ie optical flow components). The low number of training samples for each subject and the use of a test set containing subjects different from the training ones makes the search of a good CNN architecture a challenging task.
Keywords: Identificación; CNN; Flow maps; Biometrics